2012
DOI: 10.1051/0004-6361/201118350
|View full text |Cite
|
Sign up to set email alerts
|

Looking for outflow and infall signatures in high-mass star-forming regions

Abstract: Context. Many physical parameters change with time in star-forming regions. Here we attempt to correlate changes in the infall and outflow motions in high-mass star-forming regions with evolutionary stage using JCMT observations. Aims. From a sample of 45 high-mass star-forming regions in three phases of evolution, we investigate the presence of established infall and outflow tracers to determine whether there are any trends attributable to the age of the source. Methods. We obtained JCMT observations of HCO +… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
27
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 52 publications
(104 reference statements)
10
27
4
1
Order By: Relevance
“…C.1. The observed detection rate is similar to that of Klaassen et al (2012) despite the lower sensitivity, and is somewhat lower than reported by Leurini et al (2014), who had, on the other hand, a factor of ∼ 2 higher sensitivity for the same transition. These studies focused on more evolved, mostly infrared-bright clumps, many of them hosting UC-H II regions.…”
Section: Sio (8-7) Emission Towards Infrared-quiet Massive Clumpssupporting
confidence: 77%
“…C.1. The observed detection rate is similar to that of Klaassen et al (2012) despite the lower sensitivity, and is somewhat lower than reported by Leurini et al (2014), who had, on the other hand, a factor of ∼ 2 higher sensitivity for the same transition. These studies focused on more evolved, mostly infrared-bright clumps, many of them hosting UC-H II regions.…”
Section: Sio (8-7) Emission Towards Infrared-quiet Massive Clumpssupporting
confidence: 77%
“…Although infall with high accretion rates has been reported towards these types of sources (e.g. Klaassen et al 2012), the detection of the broad outflow component suggests that there is accretion ongoing not only from the envelope, but also onto the (proto)stars leading to jets. Considering that most of our clumps eventually form not only a single star, but a protocluster, these jets may originate from younger protostars nearby UC-H II regions, which have been frequently observed with high angular resolution data (e.g.…”
Section: Sio As a Tracer Of Protostellar Activity And Shocksmentioning
confidence: 99%
“…Spectral surveys have so far targeted a few selected sources in mostly distinct evolutionary stages, such as UC-H II regions, high-mass protostellar objects (HMPOs; e.g. Klaassen et al 2012), and infrared dark clouds (IRDCs; e.g. Beuther & Sridharan 2007;Vasyunina et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fuller et al 2005;Churchwell et al 2010;Klaassen et al 2012;Rygl et al 2013;Duarte-Cabral et al 2013) have been calculated for massive star precursors (e.g. HMPOs, HCH), a greater value than that associated with their lower mass counterparts (Ṁ * ∼ c 3 s G 5 × 10 −6 M yr −1 ;Shu 1977;McKee & Tan 2003).…”
Section: The Evolutionary Status Of the Ionising Sources In Sdc335mentioning
confidence: 99%